Instrument for measuring intentions to leave (2015)
The aim of this study is to show the design of an instrument that contextualises the intention to leave (IL) in terms of spaces and job content (SJC), the perceived supervisor support (PSS), the perceived peer support (PPS), the organisational extrinsic motivation (OEM), the available opportunities outside the organisation (AO) and family–work conflict (FWC) as a tool to make diagnostic evaluations of Mexican hotel companies. The method used for the design of this instrument included literature review, establishment of dimensions and items and items validation. The reliability of the instrument was evaluated through the technique of split halves, and eventually it was calculated using Cronbach’s alpha coefficient in the different components of the instrument, as an indicator of internal consistency. The correlation coefficients obtained were acceptable in 38 of the 40 and significant at 0.01 level with only two at the 0.05 level. The tool proved to be reliable as a whole and in all dimensions in the first scan. Thus, the results revealed that this instrument measures the following: the causal dimensions, intention to leave and its variables